Hematological effects of coenzyme q10 in streptozotocin-induced diabetic rats - Ercan Keskin; Deniz Uluışık (Eurasian Journal of Veterinary Sciences)
Aim: This study was conducted to evaluate the effects of Coenzyme Q10 on some hematological parameters in streptozotocin-induced diabetic rats. Materials and Methods: In the experiment, 38 healthy, adult male rats were divided into five groups. Group 1 was fed standard rat pellets for four weeks. Group 2 was administered with 0,3 ml corn oil IP daily for four weeks, group 3 was injected IP with 10 mg/kg CoQ10 daily for four weeks, group 4 was made diabetic by SC injections of 40 mg/kg streptozotocin as single daily dose for two days, group 5 was made diabetic by SC injections of streptozotocin in the same way and then was injected IP with 10 mg/kg CoQ10 daily for four weeks. In blood samples received from all animals, red blood cells (RBC) and white blood cells (WBC) counts, hemoglobin amount, hematocrit value (PCV), differential leucocyte counts and mean cell volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) were determined. Results: In diabetic rats, RBC, hemoglobin and hematocrit values were determined to be lower (p<0.05) than the control group. CoQ10 application to diabetic animals increased (p<0.05) hematocrit value compared diabetic group. Experimentally induced diabetes caused significantly (p<0.05) increments in WBC count and neutrophil percentage, while lymphocyte percentage was decreased (p<0.05) compared to control group. CoQ10 treatment to the diabetic group markedly (p<0.05) decreased the neutrophil percentage and increased the lymphocyte percentage compared to diabetic group. Conclusions: These results showed that CoQ10 treatment to diabetic rats may have some beneficial properties on hematological parameters negatively affected from diabetic injury.